2011
DOI: 10.1007/s11199-011-9959-7
|View full text |Cite
|
Sign up to set email alerts
|

Athlete or Sex Symbol: What Boys Think of Media Representations of Female Athletes

Abstract: Little research has investigated males' reactions to non-objectified media images of women, including those that depict women in instrumental activities like playing a sport. Using a survey methodology, this study examined U.S. adolescent boys' open-ended responses to images of performance athletes, sexualized athletes, and sexualized models. Participants were 104 adolescent boys from California (ages 12-17, primarily European-American). They remarked on the performance athletes' physical competence and focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 28 publications
(34 reference statements)
4
56
0
5
Order By: Relevance
“…From determination, focus, competitiveness, confidence, skill, and pride, therefore, it is hoped that print media are beginning to give female athletes the respect they deserve. Prior research shows that media outlets frequently exclude female athletes from lead stories and headlines found in national sports media (Daniels, 2008;Daniels, 2009;Duncan, 1990;Hardin, Lynn, & Walsdorf, 2005;Kane, 1996;Koivula, 1999;Lapchik & Mathews, 1999;Leath & Lumpkin, 1992;Leath & Williams, 1991;Messner, 2002;Perdersen & Whisenant, 2003;Primm, Preuhs, & Hewitt, 2007;Weber & Carini, 2012). In spite of the all-pervasive nature of sports in American culture, media seem to ignore the significance, contribution of, and importance of inclusion for women athletes (Davis, 1997;Urquhart & Crossman, 1999).…”
Section: Significance Of the Researchmentioning
confidence: 99%
“…From determination, focus, competitiveness, confidence, skill, and pride, therefore, it is hoped that print media are beginning to give female athletes the respect they deserve. Prior research shows that media outlets frequently exclude female athletes from lead stories and headlines found in national sports media (Daniels, 2008;Daniels, 2009;Duncan, 1990;Hardin, Lynn, & Walsdorf, 2005;Kane, 1996;Koivula, 1999;Lapchik & Mathews, 1999;Leath & Lumpkin, 1992;Leath & Williams, 1991;Messner, 2002;Perdersen & Whisenant, 2003;Primm, Preuhs, & Hewitt, 2007;Weber & Carini, 2012). In spite of the all-pervasive nature of sports in American culture, media seem to ignore the significance, contribution of, and importance of inclusion for women athletes (Davis, 1997;Urquhart & Crossman, 1999).…”
Section: Significance Of the Researchmentioning
confidence: 99%
“…Friedman, Santeramo, & Traina (1978, p. 293) found that trust correlated with similarity, or "Degree to which the celebrity is thought to be similar to the subject". Teenagers evaluated anti-alcohol messages as more credible when the message came from someone of the same gender as the teenager (Bochner, 1994;Brock, 1965;Daniels, 2009;Daniels & Wartena, 2011). Flanagin & Metzger (2003) cited Brock (1965), writing that "persuasiveness can be enhanced by similarity between source and receiver" (Flanagin & Metzger, 2003, p. 685).…”
Section: Credibilitymentioning
confidence: 99%
“…
AbstractPoor portrayal and perception of female athletes has a host of negative outcomes, such as objectification of women (Daniels, 2009;Daniels & Wartena, 2011) and negative reader judgment of female athletes (Knight & Giuliano, 2001). This study examines whether the gender of the sportswriter and reader affect the perception of female athletes (in terms of athleticism, respectability and interest in the sport).
…”
mentioning
confidence: 99%
“…The sexually objectified male body is muscular which suggests power, while the sexually objectified female body is thin and easily overpowered (Jhally 2009). In this issue, media portrayals of women's bodies, as well as the diminished power and heightened sexuality associated with these portrayals, shape how women are viewed in the media by U.S. boys (Daniels and Wartena 2011) and older-age Australian women (Hine 2011). U.S. women also are socialized more than men to connect their self-worth to their body shape and size, making gendered body ideals particularly deleterious for women's well-being (Oney et al 2011).…”
Section: Highlights Of Part IIImentioning
confidence: 99%
“…Female athletes, in particular, are placed in a catch-22 due to gender roles directing them to occasionally present themselves as sexually available in order to reassure the audience that they are still feminine and adhere to the feminine code of gender (Jhally 2009). Yet, as a result, their athletic skill is questioned and they are often ridiculed and criticized for presenting themselves in a sexualized manner (Daniels and Wartena 2011). Images of female athletes performing their sport evoke positive non-appearance related commentary about their athleticism, which could be used to advocate for efforts to remove sexualized images of females.…”
Section: Challenge Sexualized Media Imagesmentioning
confidence: 99%